Bismuth mediated defect engineering of epitaxial graphene on SiC(0001). (May 2019) - Hu, Tingwei; Ma, Dayan; Fang, Qinglong; Zhang, Peng; Liu, Xiangtai; Wei, Ran; Pan, Yi; Xu, Kewei; Ma, Fei
Abstract: Structural defects are commonly undesirable in materials, however, atomic-level defect engineering is promising to improve the electronic, mechanical and chemical properties of graphene, if the density and types of defects could be well controlled. Herein, bismuth-mediated defect engineering method for epitaxial graphene (EG) grown on SiC(0001) is demonstrated. It is found that single defects and defect clusters could be facilitated by evaporating Bi atoms on SiC(0001) substrate before the standard EG preparation and, Bi atoms could be thoroughly cleaned away from the EG and the unwanted doping effects of Bi will be avoided by post-annealing at higher temperature. Scanning tunneling microscopy/spectroscopy characterization reveals the atomic structures, the electronic states and the Fermi level shift of flower-like, tube-like and point defects. This study sheds light on the metal-mediated formation of defects in graphene, and provides a practical defect engineering method. Graphical abstract: Image 1